Aqueous Bismuth Titanium–Oxo Sulfate Cluster Speciation and Crystallization. Issue 51 (24th November 2017) - Molina, Pedro I.; Kozma, Karoly; Santala, Melissa; Falaise, Clément; Nyman, May
Abstract: Inorganic aqueous metal–oxo clusters are both functional "molecular metal oxides" and intermediates to understand metal oxide growth from water. There has been a recent surge in discovery of aqueous Ti‐oxo clusters but without extensive solution characterization. We use small‐angle and total X‐ray scattering, dynamic light scattering, transmission electron microscopy, and a single‐crystal X‐ray structure to show that heterometals such as bismuth stabilize labile Ti–oxo sulfate clusters in aqueous solution.[Ti22 Bi7 O41 (OH)(OH2 )30 (SO4 )12 ] 2+ features edge‐sharing between the Ti and Bi polyhedra, in contrast to the dominant corner‐linking of Ti‐oxo clusters. Bi stabilizes the Ti‐polyhedra, which are synergistically stabilized by the bidentate sulfates. Gained stability and potential functionality from heterometals is an incentive to develop more broadly the landscape of heterometallic Ti–oxo clusters. Abstract : Disassembly, re‐assembly : Titanium oxysulfate immediately self‐assembles into monodisperse polynuclear clusters upon dissolution in water. According to X‐ray scattering, these clusters are highly labile without distinct internal order. They are disassembled stepwise by adding nitric acid and Bi III ; a solution that yields a heterometallic Ti–oxo cluster.